Dynamic Capabilities: A Measurement Proposal and its Relationship with Performance - Ivan Lapuente Garrido; Caroline Kretschmer; Silvio Luis de Vasconcellos; Cláudio Reis Gonçalo (BBR: Brazilian Business Review)
Despite the relevance and growth of research into Dynamic Capabilities, certain gaps and criticisms remain. These issues are primarily related to the measurements of Dynanic Capabilities and its impacts on performance. There is a lack of empirical research that is attempting to investigate the existence, development, and orchestration of Dynamic Capabilities to support superior performance. This paper proposes and validates a scale for the measurement of Dynamic Capabilities based on Teece’s conceptual dimensions (sense, seizing and reconfiguring) through a survey presented in a highly dynamic industry and market, and by investigating the impact on performance. The results, besides validating the scale, showed Teece´s three conceptual dimensions exhibited different behavior in relation to each dimension of performance. Sense and Reconfiguration demonstrated a negative relationship with organizational performance while Seize is positively associated with performance. This may help explain some of the fuzzy results of previous studies that used proxies to measure Dynamic Capabilities.